2019
DOI: 10.1111/ele.13362
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory shapes migration and its benefits: evidence from a large herbivore

Abstract: From fine‐scale foraging to broad‐scale migration, animal movement is shaped by the distribution of resources. There is mounting evidence, however, that learning and memory also guide movement. Although migratory mammals commonly track resource waves, how resource tracking and memory guide long‐distance migration has not been reconciled. We examined these hypotheses using movement data from four populations of migratory mule deer (n = 91). Spatial memory had an extraordinary influence on migration, affecting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 52 publications
3
98
0
Order By: Relevance
“…Mounting evidence indicates that animals use memory to make movement decisions that improve resource acquisition in a heterogeneous landscape (Bailey et al, 1996;Fagan et al, 2013;Bracis et al, 2015;Abrahms et al, 2019;Merkle et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence indicates that animals use memory to make movement decisions that improve resource acquisition in a heterogeneous landscape (Bailey et al, 1996;Fagan et al, 2013;Bracis et al, 2015;Abrahms et al, 2019;Merkle et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A final caveat is that migratory behavior of mule deer is not apparently as flexible or plastic as other ungulates (Sawyer et al 2019 b ). The migratory patterns of mule deer appear to be strongly influenced by memory (Merkle et al 2019). With such rigid behaviors, mule deer may be less adaptive to rapidly changing landscapes than elk that routinely exhibit flexible migratory behavior (Eggeman et al 2016, Peters et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, Zeller et al ( 2019 ) found individual differences in resource choices in black bears even when accounting for behavioral state. Future studies might reveal that behaviorally explicit resource choices by coyotes are also individually variable, perhaps by a functional response to human presence or disturbance (as seen in wolves; Muhly et al 2019 ), spatial learning (Merkle et al 2019 ), or genotypic or phenotypic expressions (such as boldness; Wurth 2018 ).…”
Section: Discussionmentioning
confidence: 99%